A new species of Cerradicola (Leguminosae, Diocleae) from rocky outcrops in Southern Brazil - Iganci, João R.v.; Bordignon, Sérgio A.l.; Ceolin, Guilherme B.; Queiroz, Luciano P. (Phytotaxa, 2025)
Cerradicola (Leguminosae) is a monophyletic genus comprising 16 species naturally distributed across dry environments of South America. The genus reaches its highest diversity within the Cerrado and rocky outcrops of Central and Eastern Brazil, extending into Northern Argentina, Bolivia, Paraguay, and Uruguay. Species within Cerradicola are typically subshrubs that thrive in open dry habitats, often presenting underground growth. In this study, we describe Cerradicola miottoae, a new endangered species identified from a single location in Rio Grande do Sul, Southern Brazil, representing the first documented occurrence of this genus in the Brazilian Pampa. We also provide information on habitat, ecology, phenology and preliminary analysis of conservation status.